G92 What intravenous treatment is currently being administered for acute severe wheeze in childhood in emergency departments around the UK and Ireland?. (7th April 2014) - Morris, I; Lyttle, M; Doull, I; O'Sullivan, R; Powell, C
Abstract : Aims: The evidence base for the use of intravenous (IV) bronchodilator treatment in children with acute severe wheeze is limited. Thus, international guidelines vary with their recommendations. The aim of this evaluation was to examine the regimen currently used in emergency departments (EDs) of the UK and Ireland. Methods: Demographic and clinical data along with IV treatment details were collected prospectively over a ten-week period (March–June 2013) from all children aged 1–16 years presenting with acute wheeze to 24 PERUKI (Paediatric Emergency Research in the UK and Ireland) centres. Results: 3, 297 children presented to the EDs. No nebulsed magnesium sulphate (MgSO4 ) was used. 110 children (3.3%) received IV bronchodilators. Median age was 4 years. Girls [63/110 (57.3%)] were more likely to receive IV treatment (p < 0.001). IV salbutamol was used in 61/110 (55.5%), aminophylline 52/110 (47.3%) and MgSO4, 67/110(60.9%) of cases. In 16.4%, all three drugs were administered and in 31.8%, two drugs were used together. Aminophylline, salbutamol and MgSO4 were used as single agents in 21.8%, 17.3% and 12.7% respectively. MgSO4 was administered concurrently with salbutamol in 7/25 (28%) of cases where these two drugs were used together. Order of preference, when used sequentially, was most commonly, salbutamol, MgSO4 then aminophylline. Thirty different treatment IV regimens were used varying in dose, rate and duration (bolus, load and infusion) for salbutamol with variability in maximal doses given. Bolus MgSO4 was used soley with no infusion although variable doses were used. Aminophylline was most commonly used as a bolus and infusion with similar doses in most cases. Conclusions: There is huge variability in IV treatment regimen used for acute severe wheeze in children in the UK and Ireland. There is an urgent need for high quality randomised controlled trials to clarify, which is the safest and most effective regimen for this very sick group of children.